1990
DOI: 10.1128/mcb.10.9.4456
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine residues in an intron-specific region of prolactin pre-mRNA.

Abstract: N6-methyladenosine (m6A) residues occur at internal positions in most cellular and viral RNAs; both heterogeneous nuclear RNA and mRNA are involved. This modffication arises by enzymatic transfer of a methyl group from S-adenosylmethionine to the central adenosine residue in the canonical sequence G/AAC. Thus suggested following the precise localization of m6A in Rous sarcoma virus (18). In that molecule, the modified residues were found bracketing the src splice acceptor site and therefore may influence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 41 publications
4
65
1
Order By: Relevance
“…Moreover, m 6 A sites in many mRNAs were found to be concentrated within introns [97,98]. Emerging evidence from recent studies strongly supports the functional involvement of m 6 A methylation in splicing.…”
Section: Impact On Pre-mrna Splicingmentioning
confidence: 95%
“…Moreover, m 6 A sites in many mRNAs were found to be concentrated within introns [97,98]. Emerging evidence from recent studies strongly supports the functional involvement of m 6 A methylation in splicing.…”
Section: Impact On Pre-mrna Splicingmentioning
confidence: 95%
“…Thus, the presence of m 6 A has the potential to affect mRNA secondary structure as well as mRNA-protein and mRNA-snRNA interactions. Little is known of the distribution of m 6 A in nascent mRNA transcripts, but one case of its presence within an intron has been reported (Carroll et al, 1990).…”
Section: Mta Interaction With At Fip37 and Possible Functions Of M 6 mentioning
confidence: 99%
“…Methylation of the 3=UTR of mRNAs has been described since the late 1980s (36)(37)(38). Recently, studies have revealed that methylation of mRNA other than the 5=-cap structure is a common posttranscriptional modification (39).…”
Section: =Utr (mentioning
confidence: 99%